Dragon Quest monsters+. 4 - Yoshizaki, Mine; Lumsdon, David (Comic book writer) (Seven Seas Entertainment, 2019)
Lost in a sealed land and trapped by a closed-off heart, the fates of Kleo and Loran are far from certain. The land is cold, kept so by the frozen soul of the mysterious girl Marumo. Slib and Dram, meanwhile, learn valuable lessons stuck between life and death.